Effect of surface treatment on electrical properties of barium titanate/carbon nanotube/polydimethylsiloxane nanocomposites - Nawanil, C.; Panprom, P.; Khaosa-Ard, K.; Makcharoen, W.; Vittayakorn, N. (My University, 2018)
Piezoelectric-based polymer composite for flexible self-powered materials have been of interest. In this research, the effect of surface treatment on electrical properties of barium titanate/carbon nanotube/polydimethylsiloxane (BT/CNT/PDMS) composites has been studied for acquiring high performance materials. In the preparation of BT/CNT/PDMS nanocomposite, the surface of CNT and BT disperse phases were modified to introduce a functional groups. These chemical treatments devoted to improve the interfacial interactions and dispersion by introduce the strong interaction between BT, CNT and PDMS. The measured electrical outputs of the modified BT based nanocomposites showed higher output voltage than the normal composite. It is indicates that the strong interaction between fillers and polymer matrix is the important factor to improved electrical properties of the composites. Furthermore, the results also shown an enhancement of relative permittivity and maintaining a low loss of polymer nanocomposites, which indicates that the dielectric properties of composites are influenced not only by relative permittivity of the components, but also dependence on interactions between ceramics and polymers.
Keywords: Barium titanate; Carbon nanotube; Nanocomposite; Polydimethylsiloxane; Surface treatment